Correlation between hyperlipidemia and serum vitamin D levels in an adult Chinese cohort - Wang, Jinxiu; Shi, Tala; Xu, Lanlan; Li, Yanuo; Mi, Wei; Wang, Chunyang; Lu, Peng; Li, Lingyun; Liu, Ziyue; Hu, Zhiyong (Frontiers in Nutrition, 2024)
Vitamin D deficiency has emerged as a significant concern in public health due to its potential association with various metabolic disorders. This study aimed to investigate the relationship between serum vitamin D levels and the susceptibility to hyperlipidemia among adults. Using a multi-stage sampling approach, we recruited a cohort of 2072 eligible individuals aged over 18 years. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured alongside glucolipid metabolic markers, and comprehensive demographic and physical data were collected.The cohort exhibited a hyperlipidemia prevalence of 42.18%, with 19.88% demonstrating vitamin D deficiency. Notably, 23.68% of individuals with vitamin D deficiency also presented hyperlipidemia. Statistical analysis revealed a significantly higher prevalence of hyperlipidemia among those with vitamin D deficiency compared to those with sufficient levels (23.68% vs. 17.11%, P < 0.05). After adjusting for various factors including age, geographical region, exercise status, BMI, fasting glucose level, and blood pressure, lower serum 25(OH)D concentrations were found to significantly increase the risk of hyperlipidemia (Odds Ratio [OR] = 1.41; 95% CI: 1.057, 1.885; P < 0.05). Further stratification of the hyperlipidemic cohort revealed that vitamin D deficiency was associated with 1.459and 1.578-times higher risks for total cholesterol and triglyceride abnormalities, respectively, compared to those with sufficient vitamin D levels. Moreover, each 10 ng/mL decrease in serum vitamin D level corresponded to an increased risk of total cholesterol (OR = 0.82; 95% CI: 0.728, 0.974; P < 0.05) and triglyceride abnormalities (OR = 0.79; 95% CI: 0.678, 0.927; P < 0.05). However, there were no significant differences observed between vitamin D-sufficient and -deficient groups regarding Low-Density Lipoprotein (LDL) and High-Density Lipoprotein (HDL) abnormalities. These findings underscore the potential role of serum vitamin D deficiency as an independent risk factor contributing to the elevated prevalence of hyperlipidemia in the adult population.